Quantum protocol for decision making and verifying truthfulness among N‐quantum parties: Solution and extension of the quantum coin flipping game - Kazuki Ikeda; Adam Lowe (IET Quantum Communication, 2023)
Abstract The authors devised a protocol that allows two parties, who may malfunction or intentionally convey incorrect information in communication through a quantum channel, to verify each other's measurements and agree on each other's results. This has particular relevance in a modified version of the quantum coin flipping game. The key innovation of the authors’ work includes the new design of a quantum coin that excludes any advantage of cheating, by which the long‐standing problem of the fair design of the game is, affirmatively, solved. Furthermore, the analysis is extended to N‐parties communicating with each other, where multiple solutions for the verification of each player's measurement is proposed. The results in the N‐party scenario could have particular relevance for the implementation of future quantum networks, where verification of quantum information is a necessity.